IMPROVING STUDENT LEARNING MOTIVATION THROUGH THE DRILL METHOD IN LEARNING SOCIAL KNOWLEDGE OF SCIENCE - Hakop Walangadi; Larasati Ayu Lestari (International Journal of Innovations in Engineering Research and Technology, 2020)
This study aims to improve student learning motivation through the drill method in social studies learning in class V SDN 39 Hulonthalangi Gorontalo City. Researchers used classroom action research (PTK) with research subjects, namely 22 grade V students and the object of research, namely student learning motivation. Based on data analysis, it can be seen that there is an increase in student learning motivation through the drill method In social studies learning in class V SDN 39 Hulonthalangi, Gorontalo City, in the first cycle an average value of 70.56% was obtained, of course it has not reached the success indicator, meaning that it is still in the sufficient category value classification, and in the second cycle the average value is obtained. 80.34 means that it is in the good category value classification. Thus the proposed action hypothesis can be accepted. So the implementation of class action in cycle I and cycle II increases student motivation through the Drill method in social studies learning.